2008
DOI: 10.1016/j.econedurev.2007.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Does teacher testing raise teacher quality? Evidence from state certification requirements

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
50
0
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(56 citation statements)
references
References 19 publications
3
50
0
3
Order By: Relevance
“…Similarly, Rivkin et al (2005) found no relationship between teacher certification test scores and standardized test scores for grades 4-8 students. Angrist and Guryan (2007) also found that general and subject-specific test scores had no impact on teacher quality.…”
Section: Teacher Testing As An Indicator Of Content Knowledgementioning
confidence: 93%
“…Similarly, Rivkin et al (2005) found no relationship between teacher certification test scores and standardized test scores for grades 4-8 students. Angrist and Guryan (2007) also found that general and subject-specific test scores had no impact on teacher quality.…”
Section: Teacher Testing As An Indicator Of Content Knowledgementioning
confidence: 93%
“…Adgangen til å frata uegnede yrkesutøvere lisens bidrar til å holde utøverne på den smale sti, da tap av lisens vil føre til yrkesforbud. På den annen side kan høye adgangsbarrierer gjøre at de beste utøverne søker seg til andre yrker hvor investeringskostnadene ikke er like høye, spesielt hvis innsatsen for å bli godkjent ikke står i forhold til belønningen ved å vaere i yrket (Angrist & Guryan 2008).…”
Section: Kvalitet I Yrkesutøvelsenunclassified
“…Resultater fra flere amerikanske studier gir jevnt over lite støtte til at lisensiering øker kvaliteten på opplaeringen, målt som elevens laeringsutbytte (Kane, Rockoff & Steiger 2007;, ei heller blant privatskoler (Sharkey & Goldhaber 2008). Derimot viser Angrist & Guryan (2008) at laererlønningene er høyere i stater med krav til lisens, men laererne har verken en sterkere eller mer relevant utdanningsbakgrunn i disse statene sammenlignet med stater uten lisenskrav. Av den grunn konkluderer de med at lisensieringskravet først og fremst har en effekt på å redusere rekrutteringen til yrket, ikke nødvendigvis på å selektere kvalitativt bedre laerere til yrket.…”
Section: Kvalitet I Yrkesutøvelsenunclassified
“…Such a consequence is considered in light of the decline in the attractiveness of the teaching profession, which lacks occupational prestige, generous salaries, and opportunities for growth and advancement. In addition to several other non-attractive factors, such as heavy workloads and student disciplinary problems, imposing higher standards for entering the profession may discourage many qualified candidates interested in pursuing a career in education (Angrist & Guryan, 2008).…”
Section: Professional Standards: Development or Regulation?mentioning
confidence: 99%